‘Being,’ ‘doing,’ and ‘knowing’ an autoethnography of everyday ethnicity - Esteban, Rolando (Philippine Social Sciences Review, 2018)
Access online through this link: https://journals.upd.edu.ph/index.php/pssr/article/view/7915/6903